(untitled) (Bangladesh Pharmaceutical Journal, 2024)
The pandemic associated with the coronavirus disease hit Bangladesh in the year of early 2020, which was a part of the global pandemic caused by SARS-CoV-2. Six vaccines, namely Moderna, Pfizer, Covishield, Sinopharm, Sinovac and Janssen out of the eight vaccines approved by WHO, were received by the Bangladeshi people. A cross-sectional online survey comprising a descriptive questionnaire was carried out to find the effect of Covid vaccine on menstrual cycle. The longer, shorter or absence of menstrual cycles and any changes in menstrual flow were taken under consideration during the survey. The majority of the respondents (82.5%) was of 20-30 years old females. Among the total 309 responders, 210 women experienced vaccine associated side effects while fever was experienced by 36.5%, 19.1% experienced fatigue and 21.4% was reported to suffer from headache. Muscle and joint aches as well as pain, swelling and redness were noted to be 38.5% (most common) and 26.4%, respectively among others. Statistically significant (p<0.01) fluctuation was observed in menstrual cycle although mostly persisting for only one cycle. About 70% of the women noted to have regular menstrual cycle before vaccination, which was decreased to 56% including about 10-14% females experiencing different fluctuation in menstrual flow. Medications taken to alleviate the vaccine-related side effects as well as to regulate normal menstrual cycle were also recorded in the survey. This study attempted to identify the impact of COVID vaccine on menstrual cycle and no significant conclusive negative effect on women’s reproductive health was recorded. Bangladesh Pharmaceutical Journal 27(2): 149-157, 2024 (July)